The coupled role of alkali and water in governing the interfacial performance of bilayered metakaolin-based geopolymer-concrete composites: Mechanistic investigations and mix-design regulation - Zheng Chen; Jingwen Tang; Yichen Wang; Tao Su; Chaofan Yi (Applied Clay Science, 2026)

Silica nanoparticles disrupt blood–testis barrier integrity in Sertoli cells by inducing inflammation-mediated p38 MAPK pathway - Ying Wang; Wenpeng Liu; Yichen Wang; Dan Chen; Shoufang Jiang; Jinlong Li; Wenxuan Tang; Ping Lu; Xuan Shang (Reproductive Toxicology, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Engineering a tetrahedral framework nucleic acid-based nanomedicine for precise intracellular delivery of rapamycin to rescue senescent bone mesenchymal stem cells - Shibo Liu; Qiheng Yang; Hanghang Liu; Ze He; Xuehan Tang; Yichen Yang; Yunfeng Lin; En Luo (Chemical Engineering Journal, 2026)

Skin-triggered Janus physical cooling patches for prolonged evaporative cooling and superior comfort - Junyi Lu; Fuzhou Niu; Tonghuan Zhan; Heng Wang; Haojun Luo; Yichen Tang; He Wang; Xiaohua Yu; Weijie Zhang; Hao Chen; Bing Xu (Chemical Engineering Journal, 2026)

Century-long socioeconomic-air pollution transitions revealed by lake sediments in Northeast China - Yalan Tang; Yongming Han; Yichen Wang; Dongna Yan; Shaolong Sun; Qiyuan Wang; Dewen Lei; Hao Peng; Peng Yao; Zeyu Liu; Ulrike Dusek (Global and Planetary Change, 2026)

Nonlinear Dynamics and Control of Tension Leg Platform Floating Wind Turbines: A Review - Jiawen Li; Lei Yan; Guibin Chen; Yichen Jiang; Mingfu Tang (Journal of Marine Science and Engineering, 2026)
As offshore wind power development advances into deeper waters, tension leg platform (TLP) floating wind turbines stand out for their excellent motion performance, lightweight structure design, and minimal seabed footprint. This paper reviews the advancements in TLP technology, covering structural configurations, dynamic characteristics and control strategies. Particular emphasis is given to analyzing dynamic response under combined environmental loads, including nonlinear motions induced by higher-order wave forces and parametric excitations, as well as the multiphysics coupling mechanisms involving aerodynamics, hydrodynamics, servo control, and structural dynamics. The review concludes by outlining future trends in platform scaling, intelligent operation and maintenance, and multi-energy integration. Overall, this review provides strategic insights for further research and engineering applications of TLP floating wind turbines.

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Temperature-controllable antibacterial film mediated by a photoresponsive metal-polyphenol framework for long-term food preservation - Guangyang Jiang; Wenyang Sheng; Li Yang; Yichen Yang; Tingting Tang; Chenzhi Wang; Yongqiang Tian (Food Control, 2025)

Janus antistatic protective clothing for personal sweat management and electrostatic protection - Haojun Luo; Yichen Tang; Xianchang Wu; Yu Zhang; Shuqiang Min; Yijie Zhu; He Wang; Tonghuan Zhan; Zixuan Xu; Zhihao Chen; Xiaohua Yu; Heng Wang; et al. (Chemical Engineering Journal, 2025)

Development of multifunctional chitosan packaging film by plasticizing novel essential oil-based hydrophobic deep eutectic solvent: Structure, properties, and application - Guangyang Jiang; Kaiwen He; Mingrui Chen; Yichen Yang; Tingting Tang; Yongqiang Tian (Carbohydrate Polymers, 2025)

Dynamic response analysis of a fully coupled aerodynamic-hydrodynamic-mooring-anchor floating offshore wind turbine - Dongsheng Qiao; Yichen Zhou; Binbin Xu; Jianmin Qin; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

Influence of Damping Plate Size on Pitch Motion Response of Floating Offshore Wind Turbine - Jie Xu; Chuansheng Wang; Jiawen Li; Yichen Jiang; Guangyin Tang; Yi Yang (Journal of Marine Science and Engineering, 2024)
For floating offshore wind turbines, a significant pitch and roll motion response of the platform can affect the acceleration and power generation of the nacelle. The damping plate is considered a type of attachment that can be used to reduce rotational motion, but research on its anti-rotational effect is limited. The objective of this work is to analyze the impact of installing damping plates and varying their sizes on the pitch motion response of semi-submersible platforms, while also proposing optimization strategies for damping plate design. Firstly, a comparison between numerical simulations and experimental measurements validates the accuracy of the CFD calculations. Subsequently, different sizes of damping plates are proposed for the platforms, followed by simulations under various conditions. Finally, comprehensive data analysis is conducted. The findings suggest that installing damping plates enhances both the platform’s added moment of inertia and damping coefficients while simultaneously amplifying its motion response in regular waves. Furthermore, increasing the size of damping plates leads to an increase in both the added moment of inertia and motion response for the platform, whereas the damping coefficient exhibits an initial increasing trend followed by a subsequent decrease. Ultimately, it is found that increasing the distance between damping plates and the free surface significantly reduces wave-induced loads on the platform.

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Enhancement of Mn2+, Fe2+ and NH4+-N removal by biochar synergistic strains combined with activated sludge in real wastewater treatment - Shuman Deng; Qiang An; Jiali Song; Yichen Yang; Zhiruo Huang; Shuyun Feng; Chuanzhu Tang; Bin Zhao (Chemosphere, 2024)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)